2021
DOI: 10.3390/agronomy11091765
|View full text |Cite
|
Sign up to set email alerts
|

Training Systems and Sustainable Orchard Management for European Pear (Pyrus communis L.) in the Mediterranean Area: A Review

Abstract: In 2018, 23.2 Mt of pears were produced in the world across 1.3 million hectares (ha) of cultivated land. This review analyzes different training systems and management styles that have been adopted worldwide, emphasizing the European pear’s economic and environmental sustainability for the Mediterranean area of cultivation. Despite a reduced number of cultivars utilized around the world, pear presents a plethora of innovative training systems. In Europe, dwarfing rootstocks have led to reduced planting distan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(20 citation statements)
references
References 73 publications
(145 reference statements)
1
10
0
Order By: Relevance
“…According to the previous reports, B is crucial for floral bud differentiation by participating in cell wall development and membrane maintenance [42,43]; furthermore, its translocation via phloem is assisted with the presence of sorbitol in Rosaceae family plants, including pear [12,44]. Our results also found that B was typically decreased in wizened buds than in normal buds (Table S1).…”
Section: Discussionsupporting
confidence: 82%
“…According to the previous reports, B is crucial for floral bud differentiation by participating in cell wall development and membrane maintenance [42,43]; furthermore, its translocation via phloem is assisted with the presence of sorbitol in Rosaceae family plants, including pear [12,44]. Our results also found that B was typically decreased in wizened buds than in normal buds (Table S1).…”
Section: Discussionsupporting
confidence: 82%
“…Generally, the proportion of pear orchards with a high inputs was relatively large; for example, the nitrogen input to these orchards was 3 to 4 times that of orchards in developed countries under the same yield conditions (Mitcham and Elkins, 2007). However, pear orchard production in Beijing is lower than that in developed countries (Musacchi et al, 2021). Therefore, it is necessary to apply fertilizers reasonably according to the target yield and the nutrient demand characteristics of the growth in pear orchards in Beijing.…”
Section: Discussionmentioning
confidence: 99%
“…The cv. 'Conference' (Figure 2) was chosen as the reference, being the primary cultivar at the European level (EU28, before Brexit) [18]. Fruits were purchased from a local market because no commercial pear varieties are grown in the region due to the hot climate and low summer rainfall.…”
Section: Plant Materialsmentioning
confidence: 99%